2021
DOI: 10.1177/19322968211029297
|View full text |Cite
|
Sign up to set email alerts
|

Fault Tolerant Strategies for Automated Insulin Delivery Considering the Human Component: Current and Future Perspectives

Abstract: Automated Insulin Delivery (AID) are systems developed for daily use by people with type 1 diabetes (T1D). To ensure the safety of users, it is essential to consider how the human factor affects the performance and safety of these devices. While there are numerous publications on hardware-related failures of AID systems, there are few studies on the human component of the system. From a control point of view, people with T1D using AID systems are at the same time the plant to be controlled and the plant operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Meal data are crucial context information. It demonstrated that subjective trend analysis utilizing CGM can provide accurate meal timing and ground truth [ 166 ]. Similarly, in order to increase glucose prediction accuracy, ML algorithms were applied to detect daily food and physical activity patterns in [ 167 ].…”
Section: Ai In the Management Of Diabetesmentioning
confidence: 99%
“…Meal data are crucial context information. It demonstrated that subjective trend analysis utilizing CGM can provide accurate meal timing and ground truth [ 166 ]. Similarly, in order to increase glucose prediction accuracy, ML algorithms were applied to detect daily food and physical activity patterns in [ 167 ].…”
Section: Ai In the Management Of Diabetesmentioning
confidence: 99%
“…The observer gain can be designed by solving the associated LQC dual problem [47]. Given the system description (26), tuning matrices Q = Q T = H T H ≥ 0, R = R T > 0 and the performance bound γ. Then, the observer gains for the polytopic system are obtained by finding Υ and W i through the solution of the following LMI minimization problem min γ,Υ=Υ T ,W γ (30) subject to…”
Section: Design Methodsmentioning
confidence: 99%
“…The aim of this work is to provide robust and safe solutions to deal with the patientin-the-loop in AP systems. In the context of diabetes and AP systems, the patient should be considered as part of the control loop [26]. Depending on the system configuration, the patient may have to take the role of an actuator or a sensor, besides being the plant to control.…”
Section: Introductionmentioning
confidence: 99%